"I CAN'T EAT THAT MUCH": OLDER ADULTS' LIVED EXPERIENCES OF DIABETES DIETARY RECOMMENDATIONS. (11th November 2018) - Chard, S; Roth, E; Henderson, L; Girling, L; Wallace, B; Quinn, C; Eckert, K
Abstract: An estimated 33% of U.S. adults ≥65 have type 2 diabetes (T2D). "Healthy eating" is critical to managing the effects of diabetes and a core component of diabetes self-management education. Survey research indicates, however, that adults with diabetes are not meeting national diabetes dietary recommendations. The Subjective Experience of Diabetes Study, a NIA-funded qualitative study of T2D among African-American and non-Hispanic Whites in Baltimore (n=83), provides important insights into why diabetes dietary recommendations can be challenging for older adults. Systematic, thematic analyses using ATLAS.ti reveals participants perceive maintaining dietary recommendations as a daily struggle, with low appetite, comorbidities, and access to groceries impacting their success. In such contexts, healthy eating often centers on limiting consumption of specific foods (e.g., pork) or beverages (e.g., sugar-sweetened soft drinks) rather than overall diet quality. Participants also express frustration that blood glucose levels fluctuate widely even when they eat "right." The perceived gap between food consumption and diabetes control acutely undermines motivation for healthy eating. The findings highlight the need for ongoing patient-centered diabetes dietary education among older adults. Diabetes educators should be particularly attentive to older adults' focused strategies for healthy eating and the need for greater understanding of the multiple ways that diet impacts health in the context of diabetes.